PENGARUH PENERAPAN PROTOKOL PENCEGAHAN COVID-19 PADA PELAKSANAAN KONSTRUKSI PROYEK STRATEGIS NASIONAL - Nugraha Nugraha; Bambang Endro Yuwono (Universitas Trisakti, 2022)
The Covid-19 pandemic has had a significant impact on various sectors, one of which is the construction sector. Implementation elements in this sector include materials, labor, delivery or transportation processes, time and mobility that are directly related to the Covid-19 outbreak, so that it can create uncertainty, while infrastructure development is the government's focus. In an effort to overcome the impact of the pandemic in the construction sector. This study aims to learn the implementation of the Covid-19 prevention protocol in the implementation of the National Strategic Project in Margatiga Dam Project work and to determine the significance of the effect of the implementation of the Covid-19 protocol on project management in the aspects of cost, quality, time, health and safety construction. Analysis of the problem was carried out by collecting data and conducting a questionnaire related to the implementation of the Covid-19 prevention protocol at the Margatiga Dam. The data that has been collected is then analyzed or data validation is carried out using the validity test and reliability test methods. The results showed that the Covid-19 Prevention Protocol Implementation has no effect on the Work Execution Time, and the Implementation of the Covid-19 Prevention Protocol has no effect on the Cost of Work Implementation. In addition, the Implementation of the Covid-19 Prevention Protocol has an effect on Safety and Health